<u>ANSWER</u>
![h(f(x))=2x-11](https://tex.z-dn.net/?f=h%28f%28x%29%29%3D2x-11)
<u>EXPLANATION</u>
Given ![f(x)=x-7](https://tex.z-dn.net/?f=f%28x%29%3Dx-7)
and
![h(x)=2x+3](https://tex.z-dn.net/?f=h%28x%29%3D2x%2B3)
We want to find
![h(f(x))=h(x-7)](https://tex.z-dn.net/?f=h%28f%28x%29%29%3Dh%28x-7%29)
This means we substitute the function
in to another function
and evaluate.
This implies that;
![h(f(x))=2(x-7)+3](https://tex.z-dn.net/?f=h%28f%28x%29%29%3D2%28x-7%29%2B3)
We expand the parenthesis to obtain;
![h(f(x))=2x-14+3](https://tex.z-dn.net/?f=h%28f%28x%29%29%3D2x-14%2B3)
We simplify further to obtain;
![h(f(x))=2x-11](https://tex.z-dn.net/?f=h%28f%28x%29%29%3D2x-11)
Hence the correct answer is A
Answer:
5/8 or 41/8
Step-by-step explanation:
If you mean 1/8 x 5, then that equals 5/8
If mean 1/8 + 5, then that equals 41/8
Answer:
D an = 9 + 7(n-1)
Step-by-step explanation:
In the question, Max has 9 logs in the first load. But, after the seventh load he has a total of 51 logs. So the n would be your logs in the stack, which is 51. And since there is a total of 51 logs after the seventh load. It would be 9 plus 7 in parenthesis of 51 minus one, which is 50. So 50 times 7 comes down to 350 plus nine which comes down to a total of 359.
Answer:
Plese read the complete procedure below:
Step-by-step explanation:
The polynomial is p(a) = (a^4 - 6a^3 + 3a^2 + 26a – 24)
a)
1 -6 3 26 -24 |<u> 1 </u>
<u> 1 -5 -2 24</u>
1 -5 -2 24 0
The remainder is zero, then (a-1) is a factor of the polynomial
b)
1 -6 3 26 -24 |<u> 2 </u>
<u> 2 -8 10 72</u>
1 -4 5 36 48
When p(a) is divided by (a-2) the remainder 28/p(a)
1 -6 3 26 -24 |<u> - 4 </u>
<u> -4 40 172 -792</u>
1 -10 43 198 -816
When p(a) is divided by (a-2) the remainder -816/p(a)
c) I attached an image of the long division below: